Validation of Roche immunoassay for severe acute respiratory virus 2/SARS-COV-2 in South Africa - Grove, Jurette Simone (University of the Witwatersrand, Johannesburg, 2023)
Background: Serology testing is an important ancillary diagnostic to the reverse transcriptase polymerase chain reaction (RT-PCR) test for severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). We aimed to evaluate the performance of the Roche Elecsys™ chemiluminescent immunoassay (Rotkreuz, Switzerland), that detects antibodies against the SARS-CoV-2 nucleocapsid antigen, at an academic laboratory in South Africa. Methods: Serum samples were collected from 312 donors with confirmed positive SARS CoV-2 RT-PCR tests, with approval from a large university’s human research ethics committee. Negative controls included samples stored prior to December 2019 and from patients who tested negative for SARS-CoV-2 on RT-PCR and were confirmed negative using multiple serology methods (n = 124). Samples were stored at –80 °C and analysed on a Roche cobas™ 602 autoanalyser. Results: Compared with RT-PCR, our evaluation revealed a specificity of 100% and overall sensitivity of 65.1%. The sensitivity in individuals > 14 days’ post-diagnosis was 72.6%, with the highest sensitivity 31–50 days’ post-diagnosis at 88.6%. Results were also compared with in-house serology tests that showed high agreement in majority of categories. Conclusions: The sensitivity at all-time points post-diagnosis was lower than reported in other studies, but sensitivity in appropriate cohorts approached 90% with a high specificity. The lower sensitivity at earlier time points or in individuals without symptomatology may indicate failure to produce antibodies, which was further supported by the comparison against in-house serology tests.
A research report submitted for graduation for the degree MMed in Chemical Pathology, to the Faculty of Health Sciences, School of Pathology, University of the Witwatersrand, Johannesburg, 2023.
Keywords: COVID-19; SARS-CoV-2; Serology; Antibodies; Validation; Immunoglobulin G; Immunoglobulin M; UCTD; SDG-3: Good health and well-being; SDG-4: Quality education